2021
DOI: 10.1108/mbr-05-2020-0126
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the “matching managers to strategy” argument in the context of a firm’s internationalisation strategy

Abstract: Purpose This paper aims to revisit the long-standing in the management literature argument of “matching managers to strategy” in the new empirical context of the top management team (TMT) and firm internationalisation. The purpose of this paper is to examine the consequences of matching nationalities of the TMT members to the multinational corporations’ (MNC) countries of operation. Design/methodology/approach This research is based on the quantitative methods. The authors use the traditional regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 122 publications
(256 reference statements)
0
2
0
Order By: Relevance
“…Because rapid international expansion is a double-edged sword, it can either give firms a first-mover advantage or cause them to face time-compression diseconomies. Therefore, firms need to increase or decrease board gender diversity to better match the board to firms' internationalization strategy (Kaczmarek and Nyuur, 2021). For example, increasing board diversity is a more appropriate choice for firms that are expanding internationally too quickly, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Because rapid international expansion is a double-edged sword, it can either give firms a first-mover advantage or cause them to face time-compression diseconomies. Therefore, firms need to increase or decrease board gender diversity to better match the board to firms' internationalization strategy (Kaczmarek and Nyuur, 2021). For example, increasing board diversity is a more appropriate choice for firms that are expanding internationally too quickly, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research in this area has inter alia drawn on the notion of matching managers to strategies to explore how MNEs match their strategic leaders' experience and capabilities to the international scope of their operations. For example, Kaczmarek and Nyuur (2021) found that MNE performance is likely to be higher when the (foreign) nationalities of strategic leaders match the MNE's regional scope of operations. Similarly, Ruigrok, Georgakakis and Greve (2013) showed that strategic leaders at MNE headquarters with intra-regional experience are more likely to realize high performance when the MNE operates mainly within its home region.…”
Section: Horizontal Role Interdependencementioning
confidence: 99%